Mondrian e o percurso de uma poética - Silva, José Marcos Romão da [UNESP] (My University, 2010)
This dissertation titled Mondrian “The Way of Poetry” was developed during the period of the first half of 1991 to the first half of 1993 in the Graduate course “ Projeto, Arte e Sociedade “, in the Visual Poetics area of concentration.This paper proposed the approach of determinism versus creative activity in the course of the work of Mondrian which conventionalized the term “The Way of Poetry.”

Esta dissertação intitulada Mondrian “O Percurso de uma Poética” foi desenvolvida durante o período do primeiro semestre de 1991 ao primeiro semestre de 1993 no curso de Pós-Graduação “Projeto, Arte e Sociedade”, na área de concentração de Poéticas Visuais. A Dissertação propõe a abordagem do determinismo versus atividade criadora no âmbito da obra de Mondrian convencionada da expressão “O Percurso de uma Poética”.
Keywords: Belle é poque; Cartaz